Cybercrime through love scams: what women should know? / Farah Safura Muhammud and Hamizah Muhammad - Muhammud, Farah Safura; Muhammad, Hamizah (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2022)
Due to various technological advancements in the modern era, cybercrime has become a global issue. Since the outbreak of the COVID-19 pandemic, most jobs and transactions have been done virtually, compromising our global cyber security. Many people are unaware of this alarming situation leading them to become victims of cybercrime, especially the vulnerable groups of the elderly, children, and women. This conceptualstudy discusses the scammers’ modus operandi for monetary deception or militants’ recruitment through love scams. The discussion then continues with the factors that lead women to become potential victims, from the personality aspects, characteristics, and impacts after being victimised. This study concludesthat precautioussteps are necessary to avoid becoming a potential victim of cybercrime, and coping with the aftermath is equally important.